Penggunaan Radiasi Gelombang Mikro dalam Sintesis Karbon Aktif dari Serbuk Kayu Randu dan Aplikasinya untuk Menjerap Methyl Violet - Widi Astuti; Luluk Siti Zulaechah; Stefanus Lian Kristian; Dinda Tri Novira (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Randu based activated carbons were prepared using chemical activation by potassium hydroxide (KOH) and applied as a potential adsorbent for the adsorption of methyl violet dye in aqueous solution. The technique of heating during activation can affect the physical and chemical characteristics of activated carbon structure. Conventional and microwave heating techniques represent two different types of activation methods. In conventional heating, there is a thermal gradient from the hot surface of the adsorbent to its interior until steady state conditions are reached. To avoid the thermal gradient, the microwave heating technique was used. Scanning electron microscope (SEM), Fourier-transform infrared spectroscopy (FTIR) and N2 adsorption-desorption isotherm were used to study the morphology of adsorbent surface, surface chemical property and specific surface area-pore size distribution, respectively. Batch experiments were carried out to investigate the effect of pH, contact time and methyl violet concentration on sorption efficiency. The result shows that effective pH for methyl violet removal was 9. A greater amount of dye was removed with an increase in the initial concentration of dye and quasi-equilibrium reached in 180 min. The adsorption capacity of methyl violet dye by randu based activated carbon was 531.16 mg g-1.